A Pilot Study of Circulating Tumor Cells in Stage IV Non-Small Cell Lung Carcinoma - Max Haid; Edward Chesna; Mary Theodoroff; Debra K. Spaeth; Cheruppolil R. Santhosh-Kumar; Zahid N. Dar (Journal of Patient-Centered Research and Reviews, 2016)
Purpose: Measurement of the number of circulating tumor cells (CTCs) in the bloodstream has been shown to have prognostic significance in treating breast carcinoma. This pilot study was formulated to determine if stage IV non-small cell lung carcinomas similarly shed malignant cells into the circulation and if their presence has prognostic significance.